Ukraine - Morkva, Valery (Cappadocia Journal of Area Studies, 2024)
In the spring of 2024, the release of the book "Ukraine" in Turkish language marked a significant milestone in the academic and cultural dialogue between Turkey and Ukraine. Published in Ankara, the 792-page volume is the result of a collaborative effort between Ukrainian and Turkish scholars. The editors, Ismail Aydıngün from Bashkent University and Valeriy Morkva from Cappadocia University, have overseen this comprehensive exploration of Ukrainian history, designed to introduce Turkish readers to perspectives that have often been overshadowed by Russian historical narratives. This book stands out because it presents a Ukrainian view of the country’s history—something less familiar to Turkish readers compared to the more widespread Russian versions. This project offers a unique opportunity to rethink and reassess Ukraine’s past, free from the distortions of Kremlin propaganda, especially regarding topics such as the cultural interactions on the territory of modern Ukraine, the significance of the Kyiv Rus’ in the formation of the Ukrainian people, the Ukrainian-Crimean and Ukrainian-Ottoman relations in the 17th century, and the Russification policies enforced by Tsarist and Soviet authorities. These are just a few of the many themes covered, which span the course of Ukrainian history, from the Pereyaslav Council and the destruction of the Zaporozhian Sich to more recent events like the Russian annexation of Crimea, the war in Donbas, and the full-scale Russian-Ukrainian war. The book also delves into Ukrainian statehood and cultural development over the centuries, and it highlights the independence movement during the Ukrainian Revolution of 1917-21, the role of the Ukrainian Church, and the social transformations that have shaped Ukraine in the post-Soviet era. Notably, it includes a discussion of the status of the Crimean Tatars, recognizing them as the indigenous people of Crimea, and traces the historical roots of the current Russian aggression against Ukraine. By shedding light on these topics, the book provides the Turkish reader with a deeper, more nuanced understanding of Ukraine’s historical trajectory—offering a counter-narrative to the Russian imperial view that has dominated in many parts of the world, including Turkey. This is especially important today, as Russia’s ongoing war against Ukraine draws global attention to the long-standing historical tensions between the two nations. Understanding these developments through a Ukrainian lens is key to grasping the current geopolitical situation. The contributions from a diverse group of scholars make this publication particularly valuable. Among the Ukrainian authors are leading experts such as Oleksandr Halenko, who authored the chapter “Ukraine from a World History Perspective”; Viktor Horobets, who examined the Pereyaslav Council of 1654 in the broader context of Eastern European history; Heorhiy Kasyanov, who analyzed Ukraine’s development from 1991 to 2022 in terms of state, society, and the individual; and Valeriy Morkva, who contributed two chapters on the struggle for Ukrainian independence after World War I and the Russification policies of the Russian Empire and Soviet Union. Additionally, Natalia Shlikhta authored a detailed chapter on the Ukrainian Church's path to independence, tracing its journey from the early 20th century Ukrainian Revolution to the contemporary Russian-Ukrainian war. Another important contribution comes from Ibrahim Muradov, who wrote a chapter on the Russia-Ukraine war. The book also features a wealth of insights from Turkish scholars, offering complementary perspectives on key moments in Ukrainian and regional history. Abdullah Üstün of Ege University contributed a chapter on the Turks, Slavs, and Germans in the 6th century Black Sea region. Erman Şan (Mimar Sinan Güzel Sanatlar Üniversitesi)explored the Pax Hazarica and the role of the Khazar Khaganate as a focal point for the Rûs in the 9th century. Sait Ocaklı (Üsküdar Üniversitesi) examined the Crimean Khanate's northern policy in the 17th century, while Ufuk Aykol(Hacettepe Üniversitesi) wrote about the destruction of the Zaporozhian Sich and its impact on the Crimean Khanate.The nature of Ukrainian-Ottoman relations is further explored by Murat Yaşar (State University of New York at Oswego), who focused on Hetman Petro Doroshenko’s diplomatic relations with the Ottoman Empire between 1667-1678. Muhammet Şen (Ege Üniversitesi) provided an in-depth look at the Cossack-Ottoman relations during the hetmanate periods of Bohdan Khmelnytsky and his son Yuriy. Several other Turkish scholars contribute to understanding Ukraine's more recent history and its struggles for independence. Turgut Tuncel (Avrasya İncelemeleri Merkezi (AVİM)) analyzed the social-political transformations during Ukraine’s Orange Revolution and Euromaidan, while Filiz Tutku Aydın (Ankara Sosyal Bilimler Üniversitesi)offered a normative evaluation of the Crimean Tatars’ claim to indigenous status. Ayşegül Aydıngün (Orta Doğu Teknik Üniversitesi) presented an analysis of the different narratives surrounding Russia’s occupation of Ukraine, examining claims of “denazification,” “demilitarization,” and the “protection of Russians.” Legal dimensions of the Russia-Ukraine conflict were covered by Onur Uraz and Fatih Dönmez from Hacettepe Üniversitesi, who analyzed the situation through the lens of international law. Finally, Sezai Özçelik (Çankırı Karatekin Üniversitesi) offered a geopolitical analysis of the conflict from the 1994 Crimean crisis through to the 2022 Russia-Ukraine war, examining internal politics and the broader geopolitical landscape surrounding the conflict. In the words of Vasyl Bodnar, the Ukrainian Ambassador to Turkey, this academic monograph will serve as a reliable source of information on Ukraine’s history for Turkish society. In a region where Russian propaganda continues to shape public opinion, this book represents an essential step in ensuring that the truth about Ukraine and its history is heard. Given the ongoing Russian-Ukrainian war, this book plays a crucial role in the information struggle. For Ukraine, it is important in terms that it counters the Kremlin’s narratives about Ukraine being an inseparable part of Russia and brings to light the independent historical journey of the Ukrainian people. For Turkish readers, this is more than just an academic text; it is a window into the heart of a country that has long been fighting to maintain its identity, sovereignty, and historical integrity in the face of external pressures.